Bringing air pollution into the climate change equation (The World Health Organization, 2014)
As countries gear up for a major round of international climate talks next year in Paris, the growing problem of air pollution is fast becoming a vital part of the climate change and health debate. Fiona Fleck talks to Marit Viktoria Pettersen.